2020
DOI: 10.1038/s41598-020-67984-6
|View full text |Cite
|
Sign up to set email alerts
|

Non-affinity in multi-material mechanical metamaterials

Abstract: Non-affine deformations enable mechanical metamaterials to achieve their unusual properties while imposing implications for their structural integrity. The presence of multiple phases with different mechanical properties results in additional non-affinity of the deformations, a phenomenon that has never been studied before in the area of extremal mechanical metamaterials. Here, we studied the degree of non-affinity, Ŵ , resulting from the random substitution of a fraction of the struts,ρ h , that make up a lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…The use of multiple materials in auxetic structures is an area receiving attention [25][26][27][28][29][30][31]. Wang et al…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of multiple materials in auxetic structures is an area receiving attention [25][26][27][28][29][30][31]. Wang et al…”
Section: Introductionmentioning
confidence: 99%
“…[25] designed a collection of dual-material auxetic materials and they investigated the influence of design parameters on auxeticity and equivalent Young's modulus. Mirzaali et al [26,27] showed that a multi-material design could lead a wide range of elastic properties. Su et al [28] investigated a unique dual-material auxetic structure with reinforcement arches which increase the structure stiffness significantly.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical meta-materials demonstrate unprecedented mechanical properties that directly originate in their geometrical designs at different scales, in particular, small scales that are engineered to achieve unusual properties at the bulk (or macroscale) [ 1 , 2 , 3 ]. Some of these unique dimensionless properties are multi-stability [ 4 , 5 ], zero shear modulus [ 6 ], variable softening/hardening [ 7 ], snapping deformations [ 8 ] and a negative Poisson’s ratio (auxetics) [ 5 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these unique dimensionless properties are multi-stability [ 4 , 5 ], zero shear modulus [ 6 ], variable softening/hardening [ 7 ], snapping deformations [ 8 ] and a negative Poisson’s ratio (auxetics) [ 5 , 9 ]. It has been recently shown that the elastic stiffness and Poisson’s ratio of mechanical meta-materials can independently be tailored by rational design of not only the microarchitecture but also introducing bi-materials (i.e., hard and soft) [ 1 ]. Therefore, material properties of the solid constituent of meta-materials can also add a new level of design freedom in the design process of meta-materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation